PERAN KEIMIGRASIAN DALAM PENGAWASAN TERHADAP WARGA NEGARA ASING YANG MENGAJUKAN IZIN TINGGAL SEBAGAI TENAGA KERJA ASING DI KANTOR IMIGRASI KELAS 1 TPI MALANG BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN: PERAN KEIMIGRASIAN DALAM PENGAWASAN TERHADAP WARGA NEGARA ASING YANG MENGAJUKAN IZIN TINGGAL SEBAGAI TENAGA KERJA ASING DI KANTOR IMIGRASI KELAS 1 TPI MALANG BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN - admin, Admin; Wardatul Muniroh Laili Saiful; Mohammad Anton Suryadi; Muhammad Hendra (JUSTNESS - Jurnal Hukun dan Agama, 2024)
Abstract One of the roles of immigration in supervising foreign citizens who apply for residence permits as foreign workers at the TPI Malang Class 1 Immigration Office is to monitor supervision by the immigration authorities and the application of sanctions if there is misuse of the residence permit. This research was motivated by all supervision from both administrative supervision and field supervision at the TPI Malang Class 1 Immigration Office.This research aims to determine the role of immigration as well as the procedures and processes for granting residence permits to foreign citizens as foreign workers. To find out the application of sanctions for misuse of residence permits both in the process and the obstacles faced by immigration authorities based on Law Number 6 of 2011 concerning Immigration. The research approach used in preparing this research is Empirical Juridical. This research technique is interviews, field observations and document studies. The results of the research state that the role of immigration in supervising foreign citizens who apply for residence permits and abuse residence permits can be maximally enforced based on Law Number 6 of 2011 concerning Immigration. According to the Head of the Immigration Stay Permit Sub-Section at the TPI Malang Class 1 Immigration Office, this happened due to supervision carried out by immigration in accordance with Law Number 6 of 2011 concerning Immigration carried out with administrative actions and immigration pro-justice actions, as well as the granting process. for a residence permit you must apply for RPTKA to obtain IMTA, apply for VITAS, fill in the formula and then be given a Limited Stay Permit Card. And the application of sanctions for misuse of a residence permit is deportation or being placed in a detention room provided by immigration. Keywords:The role of immigration, supervision, foreign nationals, residence permits